2016
DOI: 10.1002/jmv.24666
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile and risk factors of HIV and HBV/HCV co‐infection in Fujian Province, southeastern China

Abstract: This study aimed to investigate the epidemiological features of HIV-infected subjects co-infected with HBV/HCV in Fujian Province, southeastern China, and identify the risk factors. Blood samples were collected from 2,028 HIV antibody-positive subjects in Fujian Province. Serum HBsAg and anti-HCV antibody were detected, and CD4 T cell count was measured. Of the 2,028 subjects, the prevalence of HIV-HBV, HIV-HCV, and HIV-HBV-HCV co-infections was 16.22%, 3.7%, and 0.79%, respectively. Man (OR = 1.912, 95% CI: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
1
10
0
6
Order By: Relevance
“…In this study, we found that the positive rate of HBsAg for HIV-infected patients in Shaanxi Province was 11.7%, which was higher than the general population in either China or Shaanxi Province. A number of domestic studies have shown that the positive rate of HBsAg in the HIV-infected patients was higher than that of the general population, and it ranged from 13.1% to 19.4% [30][31][32][33]. However, on the contrary, some studies have reported that in HIV-infected patients, the HBsAg positive rate was slightly lower than that of the national general population.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, we found that the positive rate of HBsAg for HIV-infected patients in Shaanxi Province was 11.7%, which was higher than the general population in either China or Shaanxi Province. A number of domestic studies have shown that the positive rate of HBsAg in the HIV-infected patients was higher than that of the general population, and it ranged from 13.1% to 19.4% [30][31][32][33]. However, on the contrary, some studies have reported that in HIV-infected patients, the HBsAg positive rate was slightly lower than that of the national general population.…”
Section: Discussionmentioning
confidence: 95%
“…One study in south-eastern China showed that the prevalence of HBV, HCV, and HBV/HCV co-infection among PLHIV was 16.22%, 3.7%, and 0.79%, respectively. 10 These rates were generally higher than other developed countries. 11 Although the widespread use of ART for HIV has significantly reduced the mortality and improved the life quality among PLHIV, 12 treatment of HIV in PLHIV with hepatitis co-infection is complicated as ART may increase the risk of hepatotoxicity and associated mortality.…”
mentioning
confidence: 86%
“…In this study, we found that the positive rate of HBsAg for HIV-infected patients in Shaanxi Province was 11.0%, which was higher than the general population in whether China or Shaanxi Province. A number of domestic studies have shown that the positive rate of HBsAg in the 10 HIV-infected patients was higher than that of the general population, and it ranged from 13.1% to 19.4% [30][31][32][33]. However, on the contrary, some studies have reported that in HIV-infected patients, the HBsAg positive rate was slightly lower than that of the national general population.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, studies reported that the rates of co-infection with HBV, HCV, and syphilis had geographic differences and varied from region to region, and based on study population and risk factors for virus acquisition [27][28][29]. In China, studies showed that among HIV-infected individuals, approximately 5.3%-19.4% were positive for HBV [30][31][32][33][34]; as assessed by the hepatitis B surface antigen (HBsAg) test, while HCV positivity (detected by the anti-HCV antibody test) varied from 2.2% to 62.4% [30][31][32][33][34][35]. However, the epidemiological and clinical profiles of HBV, HCV, and syphilis infection among HIV-infected patients remain unknown in many regions of China.…”
Section: Introductionmentioning
confidence: 99%